Caso dermatológico: Escabiose - Matos, C. (2013)
The authors describe a clinical case of a 5-months-old boy with widespread rash since the first month of life. Diffuse papular rash with intensive itching. The shaved skin was inconclusive so we performed biopsy to confirm the diagnosis of scabies. It’s a dermatosis very contagious caused by the mite Sarcoptes scabiei var. hominis. In infants skin eruption may have a polymorphic presentation with characteristic distribution.